Consumer's attitude towards digital payments: A demographic analysis - Dhrubajyoti Bordoloi; Murathoti Rajendra Nath Babu (Global Business & Finance Review (GBFR), 2024)
Purpose: The purpose of the study is to assess the knowledge and attitude of consumers towards various payment modes with special reference to digital payment methods in Nagaland State, India. Design/methodology/approach: The study is based on primary data from students, scholars, government employees, and self-employed private employees of the Nagaland state of India. The data were collected through a questionnaire. The questionnaire was standardised by using the item analysis and the items generating unfavourable t-statistics were removed. The basic data were analysed by using descriptive statistics followed by interpretation of the results. In addition to that, inferential statistics was also used for hypothesis testing. Findings: The majority of consumers were satisfied with the electronic payment option, according to the study's findings, which is encouraging for the country's lawmakers. However, consumers also make use of cash on a regular basis. Debit or credit cards are used by almost half of consumers for both in-person and online purchases. Consumers of both sexes and varying socioeconomic backgrounds have quite different sentiments about e-payments. Regarding e-payments, people with different educational backgrounds, marital statuses, management styles, and work statuses have the same attitudes. Research limitations/implications: The study was conducted in Nagaland state of India and confined to only two districts. Convenience sampling technique was used in the study. This study considered only perception towards E-Payments. Similar study may be conducted by using some other variables. Furthermore, research that are cross-sectional and longitudinal can be conducted to delve deeper into the topic. Originality/value: This study fills the apparent gap in the existing payment gateway system. It contributes to the body of research on adoption of new technologies, and specifically E- payment services. It provides with a better understanding of Consumer's attitude towards E-Payments.
Keywords: 650; E-payment; Consumers; Attitude; Unified Payment Interface (UPI)